2020
DOI: 10.1186/s13063-020-4052-6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis plan for the randomized controlled trial CardioCare MV investigating a novel integrated care concept (NICC) for patients suffering from chronic cardiovascular disease

Abstract: Background: Cardiovascular diseases are the major cause of death globally and represent a major economic burden on health care systems. For patients with heart failure, atrial fibrillation or therapy-resistant hypertension, we have developed a novel integrated care concept (NICC) which combines telemedicine with intensive support by a care center, including a call center, an integrated care network including inpatient and outpatient care providers and guideline therapy for patients (Schmidt et al. 2018 Trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…CardioCare MV was a prospective, randomized, controlled, parallel-group, open-label, blinded-observer trial that aimed to demonstrate NICC’s superiority over SoC according to three hypotheses: (1) NICC is superior to SoC in terms of the combined endpoint comprising mortality, stroke, or myocardial infarction, which should be decreased under NICC versus SoC at 12 month follow-up; (2) NICC results in a lower number of inpatient treatment days versus SoC at 12 month follow-up; (3) NICC results in a lower proportion of patients achieving the combined endpoint of mortality, stroke, myocardial infarction, or cardiac decompensation versus SoC at 12 month follow-up. Details on trial design and statistical analysis plan were formerly reported [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CardioCare MV was a prospective, randomized, controlled, parallel-group, open-label, blinded-observer trial that aimed to demonstrate NICC’s superiority over SoC according to three hypotheses: (1) NICC is superior to SoC in terms of the combined endpoint comprising mortality, stroke, or myocardial infarction, which should be decreased under NICC versus SoC at 12 month follow-up; (2) NICC results in a lower number of inpatient treatment days versus SoC at 12 month follow-up; (3) NICC results in a lower proportion of patients achieving the combined endpoint of mortality, stroke, myocardial infarction, or cardiac decompensation versus SoC at 12 month follow-up. Details on trial design and statistical analysis plan were formerly reported [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because of slow recruitment, the responsible parties endorsed the following changes: recruitment prolongation until 15th August 2019; inclusion of a further 26 cardiologists/internists as part of the UMR study centre; changes in statistical testing procedures. This amended statistical analysis plan (SAP) was presented to the Data Monitoring Committee (DMC), which approved the changes, as did the Ethics Committee of the Rostock University Medical Faculty, and subsequently published [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Starting point for template development were CIPs developed by the authors. [20][21][22]29 One of the published protocols was used as prototype for developing the CIP template. The authors next expanded the CIP template to a full protocol.…”
Section: Template Developmentmentioning
confidence: 99%
“…A.Z. is board-certified trial statistician 19 and has extensively worked on medical devices, including planning [20][21][22] and analysis of randomized controlled trials, 23 methodological work on medical devices, and its regulatory affairs 24,25 and publication recommendations. 26,27 K.K.…”
Section: Expertise Of the Reviewersmentioning
confidence: 99%
See 1 more Smart Citation